Proceedings of the 12th ACM SIGMETRICS/PERFORMANCE Joint International Conference on Measurement and Modeling of Computer Syste 2012
DOI: 10.1145/2254756.2254796
|View full text |Cite
|
Sign up to set email alerts
|

Clustered embedding of massive social networks

Abstract: -The explosive growth of social networks has created numerous exciting research opportunities. A central concept in the analysis of social networks is a proximity measure, which captures the closeness or similarity between nodes in the network. Despite much research on proximity measures, there is a lack of techniques to efciently and accurately compute proximity measures for largescale social networks. In this paper, we embed the original massive social graph into a much smaller graph, using a novel dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
(25 reference statements)
0
16
0
2
Order By: Relevance
“…There are a number of benefits of clustered low rank approximation compared to spectral regular low-rank approximation: (1) the clustered low-rank approximation preserves important structural information of a network by extracting a certain amount of information from all of the clusters; (2) it has been shown that the clustered low-rank approximation achieves a lower relative error than the truncated SVD with the same amount of memory [25]; (3) it also has been shown that even a sequential implementation of clustered low rank approximation [25] is faster than state-of-the-art algorithms for low-rank matrix approximation [20]; (4) improved accuracy of clustered low-rank approximation contributes to improved performance of end tasks, e.g., prediction of new links in social networks [26] and group recommendation to community members [29].…”
Section: Clustered Low-rank Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of benefits of clustered low rank approximation compared to spectral regular low-rank approximation: (1) the clustered low-rank approximation preserves important structural information of a network by extracting a certain amount of information from all of the clusters; (2) it has been shown that the clustered low-rank approximation achieves a lower relative error than the truncated SVD with the same amount of memory [25]; (3) it also has been shown that even a sequential implementation of clustered low rank approximation [25] is faster than state-of-the-art algorithms for low-rank matrix approximation [20]; (4) improved accuracy of clustered low-rank approximation contributes to improved performance of end tasks, e.g., prediction of new links in social networks [26] and group recommendation to community members [29].…”
Section: Clustered Low-rank Approximationmentioning
confidence: 99%
“…Link prediction is the problem of predicting formation of new links in networks that evolve over time. This problem arises in applications such as friendship recommendation in social networks [26], affiliation recommendation [29], and prediction of author collaborations in scientific publications [23].…”
Section: Link Prediction In Social Networkmentioning
confidence: 99%
“…A few examples are information retrieval using latent semantic indexing [11,4], link prediction, and affiliation recommendation in social networks [26,22,27,35,34,36,32]. A particular interest in network applications is to analyze network features as centrality, communicability, and betweenness.…”
Section: Motivationmentioning
confidence: 99%
“…In a recent publication Savas and Dhillon [30] introduced a first approach to clustered low rank approximation of graphs (square matrices) in information science applications. Their approach has proven to perform exceptionally well in a number of applications [34,32,36]. Subsequently a multilevel clustering approach was developed in order to speed up the computation of the dominant eigenvalues and eigenvectors of massive graphs [33].…”
Section: Principal Angles Assume We Have a Truncated Svd Approximatimentioning
confidence: 99%
“…We use eight different real-world networks from [1], [19], [24]. The networks are presented in Table 1.…”
Section: Datasetsmentioning
confidence: 99%